Planificación agregada para el transporte de personal y materiales en el sector hidrocarburos - Pachón Cubides, Carlos Sebastian (2025)
The objective of this study was to develop an aggregated planning for the transportation of personnel and material in a hydrocarbon sector company, using a company located in Peru as a case study. In the analysis, two key strategies were evaluated: chasing and leveling, applied to different modes of transportation, such as fixed wing, rotary wing, river and land. Through this analysis, it was observed that the chasing strategy proved to be the most appropriate for the company, since it not only presents lower operating costs compared to the leveling strategy but also allows them to meet the monthly demand accurately, which facilitates effective planning for the next year, based on the results obtained from the aggregate planning.